Daylighting availability in a living laboratory single family house and implication on electric lighting energy demand. (September 2017) - Lobaccaro, Gabriele; Esposito, Simona; Goia, Francesco; Perino, Marco
Abstract: This study aims to analyze the correlation between daylight availability and the use of artificial light in a residential building in Nordic climate. Experimental data and numerical simulations are used to compare artificial light against daylighting availability. The use of electric lighting of six users' groups and outdoor environment conditions were recorded. The daylight availability during the occupation periods has been reconstructed, using as input data the outdoor environmental variable recorded in experimental analysis. The results show that the coefficient of correlation between daylight availability and artificial lighting is low, and the artificial lighting only marginally depends on daylight availability.